Model Matematik Aliran Air Bawah Bendung - Pramudiyanto, Didik Purwantoro (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2007)
Dam is a structure which is the main function is to dammed up theflow ofthe river so that it gets the sum ofa specific volume ofthe water. The dam can be builtfrom concrete, stone, sand,. clay or combinations between them. As it function to resist the water flow ofthe river, the dam must be controlledfrom its displacement or turning over came fromthe water pressure. On the clay-typed dam, the safety value is also determinedfrom the water "rembesan ". As its affected to the stability of the dam, "rembesan" can caused the leak ofthe water to the dam and then become ruin. To anticipate those phenomenon of "rembesan" need a ''pengamatan cermat" to the "rembesan" activity of the dam so the development of "rembesan " activity can be detected, find the problem and then appropriate actions can be taken to solve them, and then more bigger problem can be avoided. The next important aspects are the dam s "rembesan" and "bocoran". On a specific circumstances, beside the "rembesan" and "bocoran" which can caused loosing the water, the "bocoran" can broke down the stability ofthe surrouding structure nearthe dam. The underground "rembesan" on a dam can be determined through numerical model with the finite element method. The utilization ofthe finite element method on the case ofthe dam "rembesan" seem like a new method compared with the finite difference method.